On the way to a Global Compact on Refugees: The "zero draft". A positive, but not yet sufficient step - Steffen Angenendt; Nadine Biehler (Stiftung Wissenschaft und Politik (SWP), 2018)
In December 2018, the United Nations General Assembly is due to adopt a 'Global Compact for Safe, Orderly and Regular Migration' and a 'Global Compact on Refugees'. These initiatives are intended to give new momentum to the international cooperation in refugee and migration policy. The first drafts are promising, but the 'Zero Draft' for the Refugee Compact is not yet ambitious enough. With regard to the ongoing negotiations on the Refugee Compact, the German government should, in particular, submit proposals on how to strengthen the implementation of the Compact, how to improve the resettlement of refugees, and how to provide sustainable financial support to host countries.
Keywords: 320